The Incidence of Nosocomial Bloodstream Infections in Children With Congenital Heart Disease Undergoing Cardiac Surgery: A Retrospective Study - Mohammad Mehdi Rajabi; Behdad Gharib; Mohammad Reza Mirzaaghayan (Acta Medica Iranica)
Congenital heart disease (CHD) is the most common congenital abnormality in children and often requires surgical intervention. These children are vulnerable to nosocomial infections (NIs), particularly bloodstream infections (BSIs), after surgery. In this study, we aimed to investigate the incidence of bloodstream infections BSIs after cardiac surgery. This retrospective study was conducted on pediatric patients refered to Children’s Medical Center Hospital, affiliated with Tehran University of Medical Sciences, from March 2022 to March 2023 for cardiac surgery. The records of 449 patients were reviewed, with 436 meeting inclusion criteria. Data were extracted from medical records, including age, weight, gender, clinical diagnoses, and blood culture results. Statistical analysis was performed using descriptive statistics (including frequency, percentage, mean, and standard deviation) and inferential statistics (including Chi-square and Independent t-test) in SPSS version 23. The results showed that the incidence of BSIs in pediatric CHD patients after cardiac surgery was 3.21%. Postoperative blood cultures revealed that Klebsiella pneumoniae was the most common pathogen (42.9%), followed by Escherichia coli and Staphylococcus epidermidis (14.3% each). No significant association was found between BSIs and gender (P=0.70), weight (P=0.06), or diagnosis (P=0.44). However, age was significantly associated with BSI incidence (P<0.001). This study provides important insights into the incidence of nosocomial BSIs in pediatric CHD patients after cardiac surgery. Our results highlight the need for stronger infection control measures and targeted antibiotic therapies to effectively manage BSIs. Further research is recommended to validate these results and improve preventive measures in pediatric cardiac units.